2006
DOI: 10.1039/b512463h
|View full text |Cite
|
Sign up to set email alerts
|

Comparative solubilisation of potassium carbonate, sodium bicarbonate and sodium carbonate in hot dimethylformamide: application of cylindrical particle surface-controlled dissolution theory

Abstract: A surface-controlled dissolution of cylindrical solid particles model is applied to potassium carbonate, sodium bicarbonate and sodium carbonate in dimethylformamide at elevated temperatures. Previously published data for the dissolution of potassium carbonate is interpreted assuming a cylindrical rather than a spherical shape of the particles, the former representing a closer approximation to the true shape of the particles as revealed by scanning electron microscopy. The dissolution kinetics of sodium carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Soda ASH Light D50 (Na 2 CO 3 ) particles exhibit geometry similar to a cylindrical and/or a rectangular shape. The images are in accord to the micrographics obtained by Forryan et al [42], who reported that the cylindrical shape of particles provides a more realistic representation of Na 2 CO 3 morphology. The process conditions, material balances, and yields of reaction products (OLP, coke, gas, and H 2 O) obtained by catalytic cracking of residual fat, oils, and grease (FOG) from grease traps at 450 C and 1.0 atm, with 5, 10, and 15% (wt.)…”
Section: Xrf Analysissupporting
confidence: 73%
“…Soda ASH Light D50 (Na 2 CO 3 ) particles exhibit geometry similar to a cylindrical and/or a rectangular shape. The images are in accord to the micrographics obtained by Forryan et al [42], who reported that the cylindrical shape of particles provides a more realistic representation of Na 2 CO 3 morphology. The process conditions, material balances, and yields of reaction products (OLP, coke, gas, and H 2 O) obtained by catalytic cracking of residual fat, oils, and grease (FOG) from grease traps at 450 C and 1.0 atm, with 5, 10, and 15% (wt.)…”
Section: Xrf Analysissupporting
confidence: 73%
“…While this might still be a suitable explanation for the observed effects, it is currently unclear whether such precipitates could be analysed using the employed techniques or if they would deteriorate as it has been observed in the presented investigations. [89][90][91] SEM analyses of a post-mortem Pt/C GDE employed during H 2 O electrolysis showed some presence of potassium resulting from the ionomer binder in the cathodic catalyst layer, as illustrated in Fig. S10 in the Supplementary Information.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the initial reaction rates must therefore originate from their initial states. We hypothesised that the difference in surface area, and hence their rates of dissolution in DMF, 56 is the main reason for the observed induction period with Base 1.…”
Section: Resultsmentioning
confidence: 99%
“…Compton et al reported major influences of the particle size, shape and temperature on the rate of dissolution of carbonates in DMF, further reinforcing the importance of characterisation of the inorganic bases in catalytic reactions. 56 Common practice in catalysis favours a finely milled inorganic base which improves the rate of the reaction. However, our results showed that the milled Base 1 resulted in a slow induction.…”
Section: Resultsmentioning
confidence: 99%